The impact of Covid‑19 on education equity: A view from Barbados and Jamaica - Blackman, Stacey N. J. (UNESCO IBE, 2021)
The outbreak of Covid-19 worldwide has presented an unprecedented challenge for the equity-in-education agenda, especially in developing countries of the Global South (e.g., the English-speaking Caribbean). This article examines the impact school closures have had in Jamaica and Barbados, and highlights the emerging disparities the global pandemic has had on education. The central organizing questions are as follows: Who was affected by school closures in Barbados and Jamaica? How did the Ministries of Education (MOEs) support curriculum and instruction during the pandemic? What challenges does Covid-19 present for MOEs? What are the implications for education after Covid-19? School closure data suggest a gender disparity, with more males than females out of school due to Covid-19 from preprimary to secondary school in Barbados and Jamaica. MOEs in the region responded to school closures primarily by increasing access to technology to facilitate remote learning. Some of the challenges with continuing education for students during Covid-19 were due to a lack of infrastructure and amenities to support remote learning. Implications for education post-Covid-19 are considered.
Keywords: Covid-19; Caribbean education; Jamaica; Barbados; school closure; equity in education